Double-layer hydrogel dressings containing l-arginine-modified polyoxometalates and methods of making the same
Patent Information
- Application Number
- CN202311606079.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-11-29
AI Technical Summary
[0008]本发明为了解决现有水凝胶普遍存在的力学强度较差,稳定性不好的问题,提供一种含有L-精氨酸修饰的多金属氧酸盐的双层水凝胶敷料及其制备方法,该方法制备的水凝胶具有良好的抑菌性能以及促进伤口愈合的功能,且具有良好的力学性能,可以为糖尿病伤口愈合提供较为理想的环境
[0023]1)本发明提出合成具有多重功能的双层水凝胶敷料,双层水凝胶敷料由两层结构和功能不同的水凝胶组成,可以最大限度地减少天然和合成水凝胶各自的缺点,成为了较具吸引力和前景的创面敷料。
Smart Images

Figure CN117582539B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogel wound dressing technology, specifically to a bilayer hydrogel dressing containing L-arginine-modified polyoxometalate and its preparation method. Background Technology
[0002] Diabetes is a common metabolic disease. Diabetic patients often experience chronic wounds that are difficult to heal due to severe hyperglycemia, making them more susceptible to bacterial infection, leading to impaired angiogenesis, persistent inflammation, and prolonged non-healing wounds. Therefore, preventing bacterial infection and reducing inflammation are crucial for the management of chronic wounds in diabetic patients.
[0003] Treating wounds with new types of dressings can effectively prevent the above problems from occurring. Good dressings need to be inexpensive, easy to use, safe and non-toxic, and have strong moisturizing properties. They also need to absorb exudate to prevent secondary infection and damage.
[0004] In recent years, hydrogels, as a biomaterial, have been found to have good biocompatibility and the ability to absorb exudates, which can basically meet people's requirements for ideal wound dressings, and have become a research hotspot in the field of wound dressings.
[0005] Hydrogels are novel materials with a three-dimensional network structure obtained through the cross-linking of polymer molecules. Both natural and synthetic polymers are primarily used to manufacture modern hydrogel wound dressings. Natural polymers have become a focus in wound dressing applications in recent years due to their excellent biocompatibility, biodegradability, non-toxicity, and low cost. However, hydrogels synthesized from these materials generally suffer from poor mechanical strength and insufficient stability.
[0006] Synthetic polymers, through the artificial design and synthesis of their molecular structures, possess excellent mechanical properties; however, their poor biocompatibility and biodegradability often limit their practical applications. Furthermore, antibiotics, as common antibacterial agents in hydrogels, while providing rapid bactericidal effects, suffer from structural instability and overuse, leading not only to strong toxic side effects on humans but also to the emergence of drug-resistant bacteria.
[0007] In summary, all existing single-function hydrogel dressings have the drawback of not providing favorable conditions for the healing of diabetic wounds. Summary of the Invention
[0008] To address the common problems of poor mechanical strength and instability in existing hydrogels, this invention provides a bilayer hydrogel dressing containing L-arginine-modified polyoxometalate and its preparation method. The hydrogel prepared by this method has good antibacterial properties and wound healing promotion function, as well as good mechanical properties, and can provide a more ideal environment for the healing of diabetic wounds.
[0009] To achieve the above objectives, the technical solution adopted by the present invention is: a method for preparing a bilayer hydrogel dressing containing L-arginine-modified polyoxometalate.
[0010] 1) Preparation of L-arginine-modified polyoxometalate composite nanoparticles;
[0011] 2) An outer hydrogel was prepared by reacting polyvinyl alcohol and hydroxypropyl methylcellulose with dimethyl sulfoxide and water as binary solvents;
[0012] 3) Add flaxseed gum, chitosan quaternary ammonium salt and the composite nanoparticles obtained in step 1) to a polyvinyl alcohol mixed precursor solution and stir until completely dissolved. Pour the solution onto the surface of the outer hydrogel and repeat freeze-thaw cycles to obtain a nanoparticle bilayer hydrogel wound dressing.
[0013] Further, the preparation method of the nanoparticles in step 1) is as follows: molybdenum carbide is dispersed into a suspension, 20%-30% hydrogen peroxide solution is added and the mixture is stirred for 12 hours. The supernatant is collected by centrifugation and freeze-dried to obtain polyoxometalate. The freeze-dried polyoxometalate and L-arginine are weighed and dissolved in Tris-HCl buffer. The mixture is stirred overnight. After the reaction is completed, the mixture is washed with water, centrifuged, and freeze-dried.
[0014] Further, the preparation method of the outer hydrogel in step 2) is as follows: add dimethyl sulfoxide to the mixture of hydroxypropyl methylcellulose and water, stir until the hydroxypropyl methylcellulose is completely dispersed and dissolved, then add polyvinyl alcohol, heat under continuous stirring until completely dissolved, perform ultrasonic vibration to remove air bubbles, and repeatedly freeze and thaw to obtain the outer hydrogel.
[0015] Further, step 3) involves preparing the polyvinyl alcohol mixed precursor solution by adding polyvinyl alcohol to deionized water, stirring for 2 hours to ensure complete dispersion of polyvinyl alcohol, and heating to 90°C under continuous stirring until the polyvinyl alcohol is completely dissolved.
[0016] Furthermore, in step 1), the mass ratio of polyoxometalate to L-arginine is 1:1-1.5.
[0017] Furthermore, in step 2), the volume ratio of dimethyl sulfoxide to water is 1-2:1.
[0018] Furthermore, in step 2), the mass concentration of hydroxypropyl methylcellulose is 3%-5%, and the mass concentration of polyvinyl alcohol is 8%-12%.
[0019] Furthermore, in step 3), the mass concentration of chitosan quaternary ammonium salt is 2%-5%, the mass concentration of flaxseed gum is 2%-5%, and the mass concentration of polyvinyl alcohol is 8%-12%.
[0020] Furthermore, the freeze-thaw cycle number is 3-5 times.
[0021] The bilayer hydrogel dressing prepared by the above method.
[0022] Compared with the prior art, the advantages and effects of the present invention are as follows:
[0023] 1) This invention proposes to synthesize a multifunctional bilayer hydrogel dressing. The bilayer hydrogel dressing consists of two layers of hydrogel with different structures and functions, which can minimize the disadvantages of natural and synthetic hydrogels, making it a more attractive and promising wound dressing.
[0024] 2) In this invention, polyvinyl alcohol is dissolved in a binary system composed of dimethyl sulfoxide (DMSO) and water. The polyvinyl alcohol is physically cross-linked by using a freeze-thaw method. At the same time, hydroxypropyl methylcellulose is added to make it self-assemble into nanofibers under the action of the binary solvent to enhance the mechanical properties of the hydrogel. A hydrogel with good mechanical properties and antifreeze properties and is safe and non-toxic is designed and synthesized, which can be used as the outer layer of a double-layer hydrogel dressing.
[0025] 2) The polyoxometalate obtained by this invention is a type of anionic metal oxide. Due to its negatively charged anionic properties and redox properties, it can generate reactive oxygen species in the inflammatory peroxidation microenvironment, which interact with the bacterial cell membrane, thereby causing the bacteria to rupture and dissolve. L-arginine is a type of amino acid with a guanidine chain. It can be converted into NO and ornithine under the action of excessive reactive oxygen species generated in the wound inflammatory peroxidation microenvironment. The generated NO can significantly promote wound healing, inhibit inflammation, has antibacterial activity, can stimulate angiogenesis, and has no adverse reactions during long-term treatment. This allows the composite hydrogel system of this invention to inhibit bacteria, prevent wound infection, and release NO during the wound healing process to promote faster wound healing.
[0026] 3) The hydrogel prepared by this invention has good biocompatibility, is basically non-irritating to wounds, has good moisturizing properties, can provide a moist environment for wounds, and reduce pain when changing dressings.
[0027] 4) The method of the present invention has mild reaction conditions and simple preparation process, which is conducive to mass production. Attached Figure Description
[0028] Figure 1 This characterizes the multifunctional properties of hydrogel samples. Among them:
[0029] (a) Tensile properties and antifreeze properties of outer hydrogels in different solvents.
[0030] (b) The load-bearing capacity of the outer hydrogel (50g).
[0031] (c) Adhesion properties of the inner hydrogel to skin, plastics, glass and wood.
[0032] (d) The bonding between the inner and outer hydrogel layers (the transparent part is the outer hydrogel, and the red part is the inner hydrogel).
[0033] (e) Photograph of the swelling of the hydrogel sample.
[0034] (f) Swelling rate of hydrogel samples.
[0035] (g) FT-IR spectrum of hydrogel.
[0036] (h) XPS spectrum of the hydrogel.
[0037] Figure 2 The mechanical properties of the hydrogel are characterized. Among them:
[0038] (a) Frequency sweep rheological analysis curve of the bilayer hydrogel.
[0039] (b) Time-scan rheological analysis curves of the bilayer hydrogel.
[0040] (c) Viscosity curve of the bilayer hydrogel.
[0041] (d) Stress-strain curve of hydrogel sample.
[0042] (e) The rupture process of hydrogel after stretching.
[0043] (f) Adhesion of hydrogel samples.
[0044] (g) Moisture content of the hydrogel sample.
[0045] (h) Water retention rate of the hydrogel sample.
[0046] Figure 3 This is for characterizing the antibacterial activity of the hydrogel samples. Among them:
[0047] (a) Antibacterial experiment on agar plates after co-culturing Escherichia coli, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa with different hydrogels.
[0048] (b) SEM images of Escherichia coli, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa on hydrogel.
[0049] (c) Images of the inhibition zones of the hydrogel against Escherichia coli, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, and Pseudomonas aeruginosa.
[0050] (d) Quantitative diagram of the inhibition zone diameter of Escherichia coli, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa.
[0051] Figure 4 This is for characterizing the cell compatibility of hydrogels. Among them...
[0052] Fluorescence micrographs (a) and cell viability (b) of NIH / 3T3 cells after treatment with hydrogel extracts of different concentrations.
[0053] (c) NIH / 3T3 cell scratch images at different time points.
[0054] (d) Quantify the in vitro scratch closure results of NIH / 3T3 cells in each experimental group.
[0055] Fluorescence micrographs (e) and cell viability (f) of HUVECs after treatment with hydrogel extracts of different concentrations.
[0056] (g) Scratch images of HUVECs cells at different time points.
[0057] (h) Quantify the in vitro scratch closure results of HUVECs cells in each experimental group.
[0058] Figure 5 These are representative images of wounds from chronic diabetes at different times.
[0059] Figure 6 To assess the healing status of diabetic wounds within the body.
[0060] (a) Healing rate of diabetic chronic wounds at different time points in each group.
[0061] (b) Remaining wound area at different time points in each group.
[0062] (c) Analysis of healing traces in chronic diabetic wounds. Detailed Implementation
[0063] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments:
[0064] The preparation method of a bilayer hydrogel dressing containing L-arginine-modified polyoxometalate comprises the following steps:
[0065] 1) Preparation of L-arginine-modified polyoxometalate composite nanoparticles;
[0066] Molybdenum carbide was dispersed in deionized water and magnetically stirred to obtain a molybdenum carbide suspension with a concentration of 0.1-0.3 g / mL. 1-2 mL of a 20-30% H₂O₂ solution was added, and the mixture was stirred for 12 h to obtain a deep blue product. The incompletely reacted raw material was precipitated by centrifugation (3000 rpm), and the supernatant was freeze-dried to obtain the polyoxometalate. The polyoxometalate and L-arginine were weighed in a mass ratio of 1:11:1.5 and placed in a glass flash flask, and dissolved separately in 2 mL of Tris-HCl buffer (pH = 8.5). The L-arginine solution was added dropwise to the polyoxometalate solution and stirred overnight. After the reaction was complete, the mixture was centrifuged three times at 3500 rpm using a 30 kDa centrifuge tube, each time for 10-15 min. After freeze-drying, the L-arginine-modified polyoxometalate was obtained and stored at 4°C for later use.
[0067] 2) Synthesis of the outer hydrogel;
[0068] Dimethyl sulfoxide (DMSO) was added to a 3-5% aqueous suspension of hydroxypropyl methylcellulose (V). DMSO V 水 The hydroxypropyl methylcellulose (HMC) was mixed with polyvinyl alcohol (PVA) at a ratio of 1:1 to 2:1 and stirred for 2 hours to ensure complete dispersion and dissolution. Then, PVA was added to the suspension to achieve a concentration of 8%-12%, and heated to 90°C with continuous stirring until the PVA was completely dissolved. The PVA-HMC mixture was ultrasonically vibrated to remove air bubbles, then transferred to a mold and placed at -20°C for 12 hours to gel. The resulting PVA-HMC hydrogel was then removed from the freezer and placed at room temperature for 3 hours. This freeze-thaw cycle was repeated 3-5 times to obtain the outer hydrogel, which was then stored at 4°C for later use.
[0069] 3) Synthesis of L-arginine-modified polyoxometalate-supported bilayer hydrogels
[0070] Flaxseed gum, chitosan quaternary ammonium salt and the composite nanoparticles obtained in step 1) were added to a polyvinyl alcohol mixed precursor solution and stirred until completely dissolved. The solution was then poured onto the surface of the outer hydrogel and subjected to repeated freeze-thaw cycles to obtain a nanoparticle bilayer hydrogel wound dressing.
[0071] Step 3) The method for preparing the polyvinyl alcohol mixed precursor solution is to add polyvinyl alcohol to deionized water, stir for 2 hours to ensure complete dispersion of polyvinyl alcohol, and heat to 90°C under continuous stirring until the polyvinyl alcohol is completely dissolved.
[0072] In step 3), the mass concentration of chitosan quaternary ammonium salt is 2%-5%, the mass concentration of flaxseed gum is 2%-5%, and the mass concentration of polyvinyl alcohol is 8%-12%.
[0073] The freeze-thaw cycle is 3-5 times.
[0074] Polyvinyl alcohol (PVA) was added to deionized water to achieve a PVA concentration of 8%-12%. The mixture was stirred for 2 hours to ensure complete dispersion of PVA, and then heated to 90°C with continuous stirring until the PVA was completely dissolved. Flaxseed gum, chitosan quaternary ammonium salt, and L-arginine-modified polyoxometalate were weighed and added to the PVA solution to achieve concentrations of 2%-5%, 2%-5%, and 0.2%-0.5%, respectively. The mixture was stirred until completely dissolved to obtain a mixture of PVA, flaxseed gum, chitosan quaternary ammonium salt, and L-arginine-modified polyoxometalate. The mixture was ultrasonically vibrated to remove air bubbles, and then transferred to a mold with an outer layer of PVA-hydroxypropyl methylcellulose hydrogel at the bottom. The mixture was placed at -20°C for 12 hours to gel. The resulting bilayer hydrogel was then removed from the freezer and placed at room temperature for 3 hours. The above freeze-thaw cycle was repeated 3-5 times to obtain a bilayer hydrogel, which was then stored at 4°C for later use.
[0075] Example 1
[0076] 2 g of molybdenum carbide was dispersed in 20 mL of deionized water and magnetically stirred. Then, 2 mL of 20% hydrogen peroxide solution was added to the molybdenum carbide suspension and the mixture was stirred for 12 h to obtain a deep blue product. The incompletely reacted raw material was precipitated by centrifugation (3000 rpm), and the supernatant was freeze-dried to obtain the polyoxometalate. 20 mg each of the polyoxometalate and L-arginine were weighed in a 1:1 mass ratio and placed in glass flash flasks, and dissolved separately in 2 mL of Tris-HCl buffer (pH = 8.5). The L-arginine solution was added dropwise to the polyoxometalate solution and stirred overnight. After the reaction was complete, the mixture was centrifuged three times (10 min each time) with water in a 30 kDa centrifuge tube at 3500 rpm. The L-arginine-modified polyoxometalate was freeze-dried and stored at 4 °C for later use.
[0077] Add 6 mL of dimethyl sulfoxide (DMSO) to 4 mL of 4% hydroxypropyl methylcellulose aqueous suspension (V DMSO V 水=3:2), stir for 2 hours to ensure complete dispersion and dissolution of hydroxypropyl methylcellulose. Then add polyvinyl alcohol (1.0 g) to the suspension and heat to 90°C with continuous stirring until the polyvinyl alcohol is completely dissolved. Sonicate the polyvinyl alcohol-hydroxypropyl methylcellulose mixture to remove air bubbles, then transfer it to a mold and place it at -20°C for 12 hours to gel. Remove the resulting polyvinyl alcohol-hydroxypropyl methylcellulose hydrogel from the freezer and place it at room temperature for 3 hours. Repeat the above freeze-thaw cycle three times to obtain the outer hydrogel, which is then stored at 4°C for later use.
[0078] Polyvinyl alcohol (1.0 g) was added to 10 mL of deionized water and stirred for 2 h to ensure complete dispersion. The mixture was then heated to 90 °C with continuous stirring until the polyvinyl alcohol was completely dissolved. 0.3 g of flaxseed gum, 0.3 g of chitosan quaternary ammonium salt, and 0.02 g of L-arginine-modified polyoxometalate were weighed and added to the polyvinyl alcohol solution. The mixture was stirred until completely dissolved, yielding a mixture of polyvinyl alcohol, flaxseed gum, chitosan quaternary ammonium salt, and L-arginine-modified polyoxometalate. This mixture was ultrasonically vibrated to remove air bubbles and then transferred to a mold with an outer layer of polyvinyl alcohol-hydroxypropyl methylcellulose hydrogel at the bottom. The mixture was placed at -20 °C for 12 h to gel. The resulting bilayer hydrogel was then removed from the freezer and placed at room temperature for 3 h. This freeze-thaw cycle was repeated three times to obtain a bilayer hydrogel, which was then stored at 4 °C for later use. Figure 1 As shown, the obtained bilayer hydrogel exhibits good stretchability and adhesion, enabling various items to adhere to the skin surface without detaching. Furthermore, the bilayer hydrogel also demonstrates good swelling properties, indicating that its volume expansion after absorbing wound exudate is minimal, thus avoiding pressure on the wound.
[0079] Example 2
[0080] 3g of molybdenum carbide was dispersed in 30mL of deionized water and magnetically stirred. Then, 1mL of 30% hydrogen peroxide solution was added to the molybdenum carbide suspension and the mixture was stirred for 12h to obtain a deep blue product. The incompletely reacted raw material was precipitated by centrifugation (3000rpm), and the supernatant was freeze-dried to obtain the polyoxometalate. 30mg each of the polyoxometalate and L-arginine were weighed at a mass ratio of 1:1.5 and placed in glass flash flasks, and dissolved separately in 2mL of Tris-HCl buffer (pH=8.5). The L-arginine solution was added dropwise to the polyoxometalate solution and stirred overnight. After the reaction was complete, the mixture was centrifuged three times with water at 3500rpm for 15min each time. The L-arginine-modified polyoxometalate was freeze-dried and stored at 4℃ for later use.
[0081] Add 5 mL of dimethyl sulfoxide (DMSO) to 5 mL of 5% hydroxypropyl methylcellulose aqueous suspension (V DMSO V 水 =3:2), stir for 2 hours to ensure complete dispersion and dissolution of hydroxypropyl methylcellulose. Then add polyvinyl alcohol (1.0 g) to the suspension and heat to 90°C with continuous stirring until the polyvinyl alcohol is completely dissolved. Sonicate the polyvinyl alcohol-hydroxypropyl methylcellulose mixture to remove air bubbles, then transfer it to a mold and place it at -20°C for 12 hours to gel. Remove the resulting polyvinyl alcohol-hydroxypropyl methylcellulose hydrogel from the freezer and place it at room temperature for 3 hours. Repeat the above freeze-thaw cycle 5 times to obtain the outer hydrogel, which is then stored at 4°C for later use.
[0082] Polyvinyl alcohol (1.0 g) was added to 10 mL of deionized water and stirred for 2 h to ensure complete dispersion. The mixture was then heated to 90 °C with continuous stirring until the polyvinyl alcohol was completely dissolved. 0.4 g of flaxseed gum, 0.4 g of chitosan quaternary ammonium salt, and 0.03 g of L-arginine-modified polyoxometalate were weighed and added to the polyvinyl alcohol solution. The mixture was stirred until completely dissolved, yielding a mixture of polyvinyl alcohol, flaxseed gum, chitosan quaternary ammonium salt, and L-arginine-modified polyoxometalate. This mixture was ultrasonically vibrated to remove air bubbles and then transferred to a mold with an outer layer of polyvinyl alcohol-hydroxypropyl methylcellulose hydrogel at the bottom. The mixture was placed at -20 °C for 12 h to gel. The resulting bilayer hydrogel was then removed from the freezer and placed at room temperature for 3 h. This freeze-thaw cycle was repeated five times to obtain a bilayer hydrogel, which was then stored at 4 °C for later use.
[0083] Example 3
[0084] 5 g of molybdenum carbide was dispersed in 20 mL of deionized water and magnetically stirred. Then, 2 mL of 25% hydrogen peroxide solution was added to the molybdenum carbide suspension and the mixture was stirred for 12 h to obtain a deep blue product. The incompletely reacted raw material was precipitated by centrifugation (3000 rpm), and the supernatant was freeze-dried to obtain the polyoxometalate. 20 mg each of the polyoxometalate and L-arginine were weighed at a mass ratio of 1:1.2 and placed in glass flash flasks, and dissolved separately in 2 mL of Tris-HCl buffer (pH = 8.5). The L-arginine solution was added dropwise to the polyoxometalate solution and stirred overnight. After the reaction was complete, the mixture was centrifuged three times (13 min each time) with water in a 30 kDa centrifuge tube at 3500 rpm. The L-arginine-modified polyoxometalate was freeze-dried and stored at 4 °C for later use.
[0085] Add 5 mL of dimethyl sulfoxide (DMSO) to 4 mL of 4% hydroxypropyl methylcellulose aqueous suspension (VDMSO V 水 =3:2), stir for 2 hours to ensure complete dispersion and dissolution of hydroxypropyl methylcellulose. Then add polyvinyl alcohol (1.0 g) to the suspension and heat to 90°C with continuous stirring until the polyvinyl alcohol is completely dissolved. Sonicate the polyvinyl alcohol-hydroxypropyl methylcellulose mixture to remove air bubbles, then transfer it to a mold and place it at -20°C for 12 hours to gel. Remove the resulting polyvinyl alcohol-hydroxypropyl methylcellulose hydrogel from the freezer and place it at room temperature for 3 hours. Repeat the above freeze-thaw cycle four times to obtain the outer hydrogel, which is then stored at 4°C for later use.
[0086] Polyvinyl alcohol (1.0 g) was added to 10 mL of deionized water and stirred for 2 h to ensure complete dispersion. The mixture was then heated to 90 °C with continuous stirring until the polyvinyl alcohol was completely dissolved. 0.5 g of flaxseed gum, 0.5 g of chitosan quaternary ammonium salt, and 0.05 g of L-arginine-modified polyoxometalate were weighed and added to the polyvinyl alcohol solution. The mixture was stirred until completely dissolved, yielding a mixture of polyvinyl alcohol, flaxseed gum, chitosan quaternary ammonium salt, and L-arginine-modified polyoxometalate. This mixture was ultrasonically vibrated to remove air bubbles and then transferred to a mold with an outer layer of polyvinyl alcohol-hydroxypropyl methylcellulose hydrogel at the bottom. The mixture was placed at -20 °C for 12 h to gel. The resulting bilayer hydrogel was then removed from the freezer and placed at room temperature for 3 h. This freeze-thaw cycle was repeated four times to obtain a bilayer hydrogel, which was then stored at 4 °C for later use. Figure 2 As shown, the resulting bilayer hydrogel exhibits excellent rheological and tensile properties, which can alleviate the mechanical damage to the wound caused by external shear stress. Furthermore, the hydrogel possesses good moisturizing properties, providing a humid environment conducive to wound healing.
[0087] The bilayer hydrogel prepared in Example 1 was used for testing. This test is used to illustrate the antibacterial properties of the hydrogel prepared in this invention.
[0088] Bacterial strain selection: Four common pathogenic bacteria, namely Escherichia coli, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus (MRSA), and Pseudomonas aeruginosa, were selected as model strains for testing.
[0089] Test methods: The antibacterial properties of hydrogel dressings were characterized by the agar plate coating method and the inhibition zone test.
[0090] (1) Agar plate spreading method: Place each group of hydrogel samples (mass 1g) into a 5mL centrifuge tube, and add 2mL of 1×10⁻⁶ agar solution accordingly. 6A CFU / mL E. coli suspension was used to ensure thorough contact with the hydrogel sample. The experiment consisted of five groups: outer hydrogel, inner hydrogel, bilayer hydrogel, bilayer hydrogel loaded with polyoxometalate (BH+POM), and the bilayer hydrogel loaded with L-arginine-modified polyoxometalate of this invention (BH+POM@L-Arg). A blank control group was also included, receiving no treatment.
[0091] The procedures for the Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, and Pseudomonas aeruginosa experimental groups were the same as above. After incubating at 37°C for 4 hours, 50 μL of the bacterial suspension was diluted to 1 mL, and 100 μL was spread onto the surface of solid nutrient agar. The mixture was then incubated at 37°C for 24 hours, and colony growth images were recorded.
[0092] (2) Inhibition zone method: 100 μL of bacterial suspension (10 6 A hydrogel sample (CFU / mL) was evenly spread onto agar medium, and then a sample with a diameter of approximately 10 mm was placed in the center of the medium. The sample was incubated at 37°C for 24 hours, and colony growth images were recorded. The diameter of the inhibition zone was quantified using an image analysis program (Image J) to evaluate the antibacterial properties of the hydrogel sample.
[0093] The hydrogels after co-culturing with bacteria were collected and fixed with formalin solution, dehydrated with a gradient of ethanol and air-dried naturally. The morphology of bacteria on the surface was observed using a scanning electron microscope.
[0094] Test results: such as Figure 3 As shown in Figure a, the number of colonies on the agar plates of the BH+POM@L-Arg hydrogel group was significantly less than that of the blank control group, and the bacterial morphology on the surface of the BH+POM@L-Arg hydrogel shrank and even broke. Figure 3 (b) indicates that the bacterial morphology was disrupted. The BH+POM@L-Arg hydrogel group had the largest diameter of the antibacterial zone. Figure 3 c, d) indicate that its antibacterial ability is better.
[0095] The bilayer hydrogel prepared in Example 1 was used for testing. This test is used to illustrate the cell compatibility of the hydrogel prepared in this invention.
[0096] Cell selection: In this experiment, NIH / 3T3 cells and HUVEC cells were used to evaluate the cell compatibility of the hydrogel.
[0097] Test Methods: The cell compatibility of hydrogels was evaluated using the MTT assay and FDA staining. First, the hydrogels were sterilized by irradiation under UV light for 24 hours, then immersed in DMEM medium at 37°C for 24 hours to obtain extracts at concentrations of 0, 25, and 50 mg / mL. The extracts were cultured in 96-well plates, with 3 × 10⁶ cells / well seeded per well. 4 NIH / 3T3 cells were cultured and incubated for 12 hours. Different concentration gradients of hydrogel extract were added sequentially to each well, with a control group of cells not receiving extract. Cells were incubated for 24 hours in a 5% CO2 incubator at 37°C. After incubation, 20 μL of MTT (5 mg / mL) was added to each well, and the cells were incubated in the dark for 4 hours. The culture medium was then removed from each well, and 150 μL of DMSO was added to each well. The cells were then shaken for 15 minutes. Finally, the absorbance (OD) of each well was measured at 570 nm using a microplate reader. s ), absorbance value of blank group (OD) b The absorbance of the control group was recorded as OD, using culture medium, MTT, and DMSO instead. c Three parallel experiments were set up for each sample. The relative cell viability of each group was calculated.
[0098] Cells were cultured in 24-well plates at 37°C for 12 hours using DMEM medium containing 10% fetal bovine serum and 1% penicillin-streptomycin. Each well was then replaced with 1 mL of hydrogel extract medium (0, 25, or 50 mg / mL). After another 24 hours of incubation, the hydrogel medium was discarded. Each well was stained with 100 μL of 0.01% FDA for 5 minutes, washed with PBS, and cell morphology images were recorded using a fluorescence microscope. Cell viability was calculated using ImageJ software based on the cell morphology images.
[0099] To further evaluate the effect of hydrogel on cell migration, a cell scratch assay was performed. Healthy cells were seeded into 6-well plates, allowing them to form a single adherent monolayer. The culture medium was then discarded, and the monolayer was vertically scraped with a sterile 20 μL pipette tip to create regular scratches. Cell debris was washed away with PBS buffer, and fresh culture medium was added. Next, 2 mL of hydrogel extraction buffer was added to each well. A blank control was prepared using PBS buffer. After incubation at 37°C for 24 h, the scratch pattern in each well was observed using an inverted microscope to assess the effect of the hydrogel on cell migration. The scratch area was measured using ImageJ software, and cell migration rate was calculated.
[0100] Test results: such as Figure 4As shown in a, b, e, and f, after 24 hours of incubation, the cell viability was above 90%, indicating that the hydrogel has good biocompatibility and no toxic side effects on normal cells. Furthermore, the cell scratch area in the BH+POM@L-Arg hydrogel group was significantly reduced. Figure 4 c, d, g, h) demonstrate that BH+POM@L-Arg hydrogel can significantly promote cell migration.
[0101] The bilayer hydrogel prepared in Example 1 was used for testing. This test was used to illustrate the ability of the bilayer hydrogel prepared in this invention to promote the healing of diabetic wounds.
[0102] Test subjects were selected: 8-week-old male KM mice with an initial weight of 25-30g were used.
[0103] Test Method: Eight-week-old male KM mice were acclimatized for one week, fasted for 12 hours, and then injected with streptozotocin STZ (prepared with sodium citrate buffer, concentration 1%) at a single dose of 180 mg / kg. Feed was added 2 hours after injection. Four days after injection, fasting blood glucose was measured at 9:00 AM and 3:00 PM. Blood was collected from the tail vein, and a blood glucose level above 16.7 mmol / L was considered a successful model. Mice exhibited polydipsia, polyuria, and polyphagia after successful modeling.
[0104] Diabetic KM mice (average weight 40g) that successfully developed the model were housed in a controlled environment (12:12 hour diurnal rhythm, constant temperature 23±2℃, humidity 50%-60%), with free access to water and food. Mice were anesthetized via intraperitoneal injection, and their dorsal hair was shaved using an electric shaver. A circular wound approximately 10mm in diameter was then created on the back of each mouse. The experimental groups were treated with outer hydrogel, inner hydrogel, bilayer hydrogel, bilayer hydrogel loaded with polyoxometalates, and bilayer hydrogel loaded with L-arginine-modified polyoxometalates, respectively. The control group received no treatment except for rinsing with PBS. Wounds in different groups were photographed at 0, 3, 6, 9, 12, and 15 days post-surgery, and the wound area was quantified using ImageJ software for comparison.
[0105] Test results: such as Figure 5 and Figure 6 As shown, during the entire healing process, the BH+POM@L-Arg group had the highest wound healing rate (92.5% ± 0.83%) and the smallest remaining wound area (0.061 ± 0.017 cm²). 2 Throughout the process, the wound healing rate in the experimental group was consistently lower than that in the blank control group. This indicates that BH+POM@L-Arg hydrogel has a role in promoting wound healing in diabetic patients.
[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a bilayer hydrogel dressing containing L-arginine-modified polyoxometalate, characterized in that, The steps are as follows: 1) Preparation of L-arginine-modified polyoxometalate composite nanoparticles; 2) An outer hydrogel was prepared by reacting polyvinyl alcohol and hydroxypropyl methylcellulose with dimethyl sulfoxide and water as binary solvents; 3) Add flaxseed gum, chitosan quaternary ammonium salt and the composite nanoparticles obtained in step 1) to a polyvinyl alcohol mixed precursor solution and stir until completely dissolved. Pour the solution onto the surface of the outer hydrogel and repeat freeze-thaw cycles to obtain a nanoparticle bilayer hydrogel wound dressing. Step 1) The preparation method of the nanoparticles is as follows: Molybdenum carbide is dispersed into a suspension, 20%-30% hydrogen peroxide solution is added and the mixture is stirred for 12 hours. The supernatant is collected by centrifugation and freeze-dried to obtain polyoxometalates. The freeze-dried polyoxometalates and L-arginine are weighed and dissolved in Tris-HCl buffer. The mixture is stirred overnight. After the reaction is completed, the mixture is washed with water, centrifuged and freeze-dried. Step 2) The preparation method of the outer hydrogel is as follows: Dimethyl sulfoxide is added to the mixture of hydroxypropyl methylcellulose and water, and stirred until the hydroxypropyl methylcellulose is completely dispersed and dissolved. Then polyvinyl alcohol is added and heated until completely dissolved under continuous stirring. Ultrasonic vibration is performed to remove air bubbles, and the outer hydrogel is obtained by repeated freeze-thaw cycles. Step 3) The method for preparing the polyvinyl alcohol mixed precursor solution is to add polyvinyl alcohol to deionized water, stir for 2 h to ensure complete dispersion of polyvinyl alcohol, and heat to 90 °C under continuous stirring until the polyvinyl alcohol is completely dissolved. In step 1), the mass ratio of polyoxometalate to L-arginine is 1:1-1.
5. In step 2), the volume ratio of dimethyl sulfoxide to water is 1-2:
1.
2. The method for preparing the bilayer hydrogel dressing containing L-arginine-modified polyoxometalate according to claim 1, characterized in that, In step 2), the mass concentration of hydroxypropyl methylcellulose is 3%-5%, and the mass concentration of polyvinyl alcohol is 8%-12%.
3. The method for preparing a bilayer hydrogel dressing containing L-arginine-modified polyoxometalate according to claim 1 or 2, characterized in that, In step 3), the mass concentration of chitosan quaternary ammonium salt is 2%-5%, the mass concentration of flaxseed gum is 2%-5%, and the mass concentration of polyvinyl alcohol is 8%-12%.
4. The method for preparing the bilayer hydrogel dressing containing L-arginine-modified polyoxometalate according to claim 3, characterized in that, The freeze-thaw cycle is 3-5 times.
5. The bilayer hydrogel dressing prepared by the method described in claim 1.
Citation Information
Patent Citations
Thermo-sensitive and long-acting antibacterial arginine-group hydrogel dressing and preparation method thereof
CN105797193A
Preparation method of porous nano-oxide modified chitosan medical hydrogel dressing
CN108992702A